2018
DOI: 10.1186/s40360-017-0193-y
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive tolerance to NSAIDs in the anterior cingulate cortex is mediated via endogenous opioid mechanism

Abstract: BackgroundIn the past decade several studies have reported that in some brain areas, particularly, in the midbrain periaqueductal gray matter, rostral ventro-medial medulla, central nucleus of amygdala, nucleus raphe magnus, and dorsal hippocampus, microinjections of non-steroidal anti-inflammatory drugs (NSAIDs) induce antinociception with distinct development of tolerance. Given this evidence, in this study we investigated the development of tolerance to the analgesic effects of NSAIDs diclofenac, ketorolac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 29 publications
0
15
1
Order By: Relevance
“…Then, the general toxicity of alkenes, alkynes and -cyclo compounds are greater than alkanes group 41 . Accordingly, the presence of more alkyl and quaternary nitrogen group contributes to the higher toxicity by obidoxime and K075, respectively 42 . This fact is in very good agreement with their acute toxicity data.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the general toxicity of alkenes, alkynes and -cyclo compounds are greater than alkanes group 41 . Accordingly, the presence of more alkyl and quaternary nitrogen group contributes to the higher toxicity by obidoxime and K075, respectively 42 . This fact is in very good agreement with their acute toxicity data.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the analgesic effects of NSAIDs are mediated via the endogenous opioid mechanism in the trigeminovascular pathway, mainly including the trigeminal nucleus, limbic system, prefrontal cortex and higher sensory cortex ( Hodkinson et al, 2015 , Tsagareli et al, 2012 , Tsiklauri et al, 2018 ). In turn, changes in the brain regions involved in the pathway could affect the pain-alleviating effects.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the above mentioned, substantial neuroimaging studies have reported that functional impairments with multiple brain networks including the limbic system, are related to the neuropsychological mechanism underlying the chronic pain [26]. Further, some fMRI studies have demonstrated that neural mechanisms of NSAIDs may be involved in the pathophysiological and therapeutic response [27,28]. On the other hand, anxiety and depression are the common comorbidities associated with chronic pain, which result in aggravation of pain and di culty of treatment [29].…”
Section: Discussionmentioning
confidence: 99%